Peran Personalized Service, Komunikasi Interpersonal, dan Hospitality Behavior Front Office dalam Meningkatkan Positive Guest Experience Tamu Hotel - Miftakul Isma; Irfa Arista; Agus Sudarsono (TOBA: Journal of Tourism, Hospitality, and Destination, 2026)
This study aims to analyze the role of personalized service, interpersonal communication, and front office hospitality behavior in improving the hotel guest experience. This study used a quantitative explanatory approach with data collection techniques through questionnaires to 41 respondents who were hotel guests. Data were analyzed using multiple linear regression to test the influence of each variable on positive guest experience. The results showed that hospitality behavior has a positive and significant influence on positive guest experience, personalized service and interpersonal communication did not affect positive guest experience. These findings indicate that behavioral aspects, such as empathy, friendliness, and staff responsiveness, are more decisive in shaping the guest experience than technical service aspects. Nevertheless, personalized service and interpersonal communication still play a role as supporting factors that strengthen the quality of interactions between staff and guests. This study concludes that improving hospitality behavior is key to creating a positive guest experience. The implication is that hotel management needs to prioritize the development of front office staff's soft skills and ensure consistency in the implementation of behavior-based services to increase the competitiveness of the hotel industry.